Clinacanthus nutans extract lowers periodontal inflammation under high-glucose conditions via inhibiting NF-κB signaling pathway - Thongyim, Saruda; Wright, Thomas A.; Sattayawat, Pachara; Kaewkod, Thida; Baillie, George S.; Tragoolpua, Yingmanee; Jangsutthivorawat, Siriphorn; Panya, Aussara (Frontiers in Pharmacology, 2024)
Periodontal disease is more prevalent in patients with diabetes, and it has a negative impact on their quality of life. Inhibiting the infection and inflammation processes that cause periodontal disease can reduce the severity of the disease and chances of serious complications. In this study, we aimed to demonstrate the effectiveness of Clinacanthus nutans extract in reducing the inflammation in gingival fibroblast cells induced by Porphyromonas gingivalis lipopolysaccharide (LPS). Stimulation with LPS under high glucose conditions led to increased inflammation compared to low glucose conditions. Treatment of C. nutans extract significantly reduced the expression of these pro-inflammatory cytokines and chemokines. At a concentration of 50 µg/mL, it reduced the relative expression of IL6, IL8, and CXCL10 to 0.51 ± 0.09, 0.6 ± 0.19, and 0.09 ± 0.02, respectively, compared to the non-treatment control, accompanied by a decrease in secreted protein as measured by ELISA. Additionally, application of C. nutans extract markedly suppressed the NF-κB signaling pathway by reducing the phosphorylated form of IκBα, NF-κB p65, and nuclear translocation of NF-κB, along with a decrease in COX2, a key mediator in the inflammatory pathway. Furthermore, analysis of RNA sequencing data indicated that the extract clearly reversed the gene expression changes induced by LPS. This was particularly true for the signaling mediators and inflammatory genes in response to NF-κB, JAK/STAT, and TNF signaling pathways. Our finding highlights the potential of C. nutans extract to alleviate inflammation and suggest its potential as a treatment for periodontal disease in patients with diabetes.